MENDISIPLINKAN PRAKTIK KETERAMPILAN BERPIKIR DAN KETERAMPILAN VERBAL UNTUK MENINGKATKAN KUALITAS DIRI - Irene Nusanti (SENDIKRAF Jurnal Pendidikan Seni dan Industri Kreatif, 2020)
Student’s character is much exposed due to the brawl they do and the quality of their improper behavior they show. Relating to this issue, this article is intended to describe of (1) ways disciplining the practice of thinking skill and verbal skill to improve self quality, and (2) steps of disciplining the practice of thinking skill and verbal skill to make student’s behavior and communication consistent and well-guided in order to create a great school habit and culture. By habituating to practice a logical and creative thinking skill, students will have solutions to every problem they encounter. Also, by habituating to speak positive and fruitful words, their verbal skills will be well-trained. The steps of disciplining the practice of thinking skill and verbal skill are done through disciplining oneself by developing the talent the students have, while disciplining others is done by developing giving skill and serving skill. By having the students practice their thinking skill, verbal skill wholeheartedly and continuously, as well as having a reflection time periodically, either at school, at home, or in the community, their self quality will improve gradually. The final goal is to have smart students with a great character